Hypoxia‐driven variations in iron and manganese shuttling in the Baltic Sea over the past 8 kyr. (30th October 2015) - Lenz, Conny; Jilbert, Tom; Conley, Daniel J.; Slomp, Caroline P.
Abstract: The Baltic Sea has experienced three major intervals of bottom water hypoxia following the intrusion of seawater circa 8 kyr ago. These intervals occurred during the Holocene Thermal Maximum (HTM), Medieval Climate Anomaly (MCA), and during recent decades. Here we show that sequestration of both Fe and Mn in Baltic Sea sediments generally increases with water depth, and we attribute this to shelf‐to‐basin transfer ("shuttling") of Fe and Mn. Burial of Mn in slope and basin sediments was enhanced following the lake‐brackish/marine transition at the beginning of the hypoxic interval during the HTM. During hypoxic intervals, shelf‐to‐basin transfer of Fe was generally enhanced but that of Mn was reduced. However, intensification of hypoxia within hypoxic intervals led to decreased burial of both Mn and Fe in deep basin sediments. This implies a nonlinearity in shelf Fe release upon expanding hypoxia with initial enhanced Fe release relative to oxic conditions followed by increased retention in shelf sediments, likely in the form of iron sulfide minerals. For Mn, extended hypoxia leads to more limited sequestration as Mn carbonate in deep basin sediments, presumably because of more rapid reduction of Mn oxides formed after inflows and subsequent escape of dissolved Mn to the overlying water. Our Fe records suggest that modern Baltic Sea hypoxia is more widespread than in the past. Furthermore, hypoxia‐driven variations in shelf‐to‐basin transfer of Fe may have impacted the dynamics of P and sulfide in the Baltic Sea thus providing potential feedbacks on the further development of hypoxia. Key Points: Baltic Sea hypoxia alters shelf‐to‐basin transfer of Fe and Mn Extended hypoxia leads to more limited Mn sequestration in sediments Modern hypoxia is more widespread than earlier in the Holocene